Cloning and characterization of the ferric enterobactin receptor gene (pfeA) of Pseudomonas aeruginosa. - Dean, C R (1993)
Pseudomonas aeruginosa K407, a mutant lacking a high-affinity 80,000-molecular-weight ferric enterobactin receptor protein (80K protein), exhibited poor growth (small colonies) on iron-deficient succinate minimal medium containing ethylenediamine-di(o-hydroxyphenylacetic acid) (EDDHA) and enterobactin. The gene encoding the ferric enterobactin receptor was cloned by complementation of this growth defect. The complementing DNA was subsequently localized to a 7.1-kilobase-pair (kb) SstI-HindIII fragment which was able to restore synthesis of the 80K protein in strain K407 and also to direct the synthesis of high levels of a protein of the same molecular weight in the outer membranes of Escherichia coli fepA strains MT912 and IR20. Moreover, the fragment complemented the fepA mutation in MT912, restoring both growth in EDDHA-containing medium and enterobactin-dependent uptake of 55Fe3+. Expression of the P. aeruginosa receptor in E. coli IR20 was shown to be regulated by both iron and enterobactin. The complementing DNA was further localized to a 5.3-kb SphI-SstI fragment which was then subjected to deletion analysis to obtain the smallest fragment capable of directing the synthesis of the 80K protein in the outer membrane of strain K407. A 3.2-kb DNA fragment that restored production of the receptor in strain K407 was subsequently isolated. The fragment also directed synthesis of the protein in E. coli MT912 but at levels much lower than those previously observed. Nucleotide sequencing of the fragment revealed an open reading frame (designated pfeA for Pseudomonas ferric enterobactin) of 2,241 bp capable of encoding a 746-amino-acid protein with a molecular weight of 80,967. The PfeA protein showed more than 60% homology to the E. coli FepA protein. Consistent with this, the two proteins showed significant immunological cross-reactivity.